Development of Multi-Representation Test As A Solution to Train High-Order Thinking Skills High School Students in Newton’s Law - Hidayah Zuliana Puspitaningrum; Wasis; Tjipto Prastowo (IJORER : International Journal of Recent Educational Research, 2021)
This research aims to develop a multi-representation based test instrument that can be used to measure students' higher-order thinking skills, especially in Newton's law material. development procedures used the Plomp development model, the stages were design, construction/ realization, test, evaluation, revision, and implementation. The subjects in this study were 36 students of class X at one of High School in Surabaya. At the implementation stage, tests were given to students and analysed using Rasch analysis with help of Winstep software. The multi-representation test instrument in question was a question in the form of an essay with a representation model consisted of visual, verbal, and mathematical representations adapted to the cognitive domain of Bloom's taxonomy of higher-order thinking. Data collection techniques were validation of instruments and tests. The results of this study were 9 items of valid test instruments based on logical validity and empirical validity and a reliable instrument based on calculations using the Alpha Cronbach equation. Based on the results of this research can be concluded that multi-representation test can be train high order thinking skills students. Study with multi-representation test is expected to be able to make students are easier to develop high order thinking skill, in this research students can be categorized as having sufficient high-order thinking skills.